The Benefit of a Complete over a Successful Reperfusion Decreases with Time. Issue 5 (27th January 2023) - Maïer, Benjamin; Finitsis, Stephanos; Mazighi, Mikael; Lapergue, Bertrand; Marnat, Gaultier; Sibon, Igor; Richard, Sebastien; Viguier, Alain; Cognard, Christophe; Gory, Benjamin; Olivot, Jean‐Marc; ,
Abstract : Objective: Time from stroke onset to reperfusion (TSOR) is strongly associated with outcomes after endovascular treatment. A near‐to‐complete or complete reperfusion (modified Treatment in Cerebral Ischemia [mTICI] 2c–3) is associated with improved outcomes compared with a successful reperfusion (mTICI 2b). However, it is unknown whether this association remains stable as TSOR increases. Therefore, we sought to investigate the association between TSOR and outcomes according to the reperfusion status. Methods: We analyzed data from the Endovascular Treatment in Ischemic Stroke registry, a prospective, observational, multicentric study of acute ischemic stroke patients treated with endovascular treatment in 21 centers in France. We included patients with anterior occlusions (M1, internal carotid artery, tandem), with a known time of symptom onset. Outcomes were early neurological improvement at 24 hours and favorable outcome (modified Rankin Scale between 0 and 2) at 90 days. Results: Overall, 4, 444 patients were analyzed. Compared with a mTICI 2b, a mTICI 2c‐3 at 1 hour was associated with higher mean marginal probabilities of early neurological improvement (25.6%, 95% CI 11.7–39.5, p  = 0.0003) and favorable outcome (15.2%, 95% CI 3.0–27.4, p  = 0.0143), and progressively declined with TSOR. The benefit of a mTICI 2c‐3 over a mTICI 2b was no longer significant regarding the rates of early neurological improvement and favorable outcome after a TSOR of 414 and 344 minutes, respectively. Interpretation: The prognostic value of a complete over a successful reperfusion progressively declined with time, and no difference regarding the rates of favorable outcome was observed between a complete and successful reperfusion beyond 5.7 hours. ANN NEUROL 2023;93:934–941